Molecularly Engineered Unparalleled Strength and Supertoughness of Poly(urea-urethane) with Shape Memory and Clusterization-Triggered Emission - Wang, Xiaoyue (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.